Holocene and pre-Holocene temporary disappearance of the George VI Ice Shelf, Antarctic Peninsula - Bentley, Michael J.; Hjort, Christian; Ingólfsson, Ólafur (Antarctic Science, 2001)
We present evidence for the absence of the George VI Ice Shelf during a brief period in the mid-Holocene and during one or more earlier interstadials or interglacials. Barnacle Bathylasma corolliforme shells sampled from ice shelf moraines at Two Step Cliffs on Alexander Island have been dated to c, 5750–6000 14C yr BP(c. 6550–6850 cal yr BP) and imply seasonally open water in the George VI Sound during this period. Other shells are beyond the range of radiocarbon dating and imply open water during one or more previous interglacial or interstadial period, prior to 40 000 14C yr BP. Our results show that the ongoing collapse of some Antarctic Peninsula ice shelves is not unprecedented.
Keywords: Antarktis; geomorfologi; glasiologi; holocene; isshelf

Current measurements near Ronne Ice Shelf: implications for circulation and melting - Foldvik, Arne; Gammelsrød, Tor; Nygaard, E.; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2001)
We present the first year-long current meter records ever obtained near the floating Filchner-Ronne Ice Shelf in the Weddell Sea. The currents are steered along the ice front, but in the lower layer where the bottom topography is descending toward the west the current has a component toward the ice front of about 3 cm s−1. During winter the temperature stayed near the surface freezing point, while the salinity increased, indicating that ice was formed and brine released. The seasonal variation in salinity was 0.15±0.05 psu, corresponding to the formation of 1–2 m of ice on a shelf depth of 400 m. The transport of High-Salinity Shelf Water (HSSW) into the ice shelf cavity was found to be of the order 0.5×106 m3 s−1. The production of this water due to oscillating tides and off shelf winds was found to be of the same order of magnitude. In contact with glacial ice at great depths, and because of the depression of the freezing point, the HSSW is transformed to Ice Shelf Water (ISW) by cooling and melting processes. The melting rate was estimated to 1×1011 ton yr−1. This corresponds to the melting of 0.2 m ice per year if the melting is evenly distributed over the Filchner-Ronne Ice Shelf. If the melting is concentrated along a path from the Berkner Shelf around the Berkner Island to the Filchner Depression, then melting rates up to 7 m yr−1 must be expected. A comparison of HSSW characteristics in the Ronne Depression, our winter observations on the Berkner Shelf, and the ISW flowing out of the Filchner Depression indicates that very little water passes through the cavity from the Ronne to the Filchner Depression. It appears that most of the ISW originating from processes on the Berkner Shelf escapes the cavity in the Filchner Depression. This leaves the Berkner Shelf as the important source of ISW and subsequently of the Weddell Sea Bottom Water formed from ISW.
Keywords: Antarktis; Weddellhavet; havstrømmer; isshelf; oseanografi